THE PROGRESS OF THE TECHNIQUES OF LEGAL MEDICINE AND SCIENTIFIC POLICE - PIGA RIVERO, Antonio; ALFONSO GALÁN, Mª Teresa; PIGA, Henrik; FERNÁNDEZ-LAREDO, Asunción; BARREDA CABANILLAS, Íñigo (MEDECINE LEGALE DROIT MEDICAL, 2025)
The article retraces the evolution of the medico-legal and criminalistics techniques from the XIXth Century to the present. But the efficacy and fairness of justice, in addition to the results of the evidence found and collected, depends also of the guarantees of the quality in all the procedures performed. In the article are reviewed the in the EU existing norms and methods of handle of medico-legal and scientific police evidence, in order to ensure that the judicial decisions can be fair and transparent in a reality in which the AI is everywhere.